Exploring the Feasibility of Implementing Online Learning at the Faculty of Science: A Case Study - Amina Shtewi (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. In recent years, the education sector in Libya have been affected by wars and political fluctuations, impacting the quality and availability of education. There have been challenges in providing the necessary educational resources, as well as in training and qualifying teachers. E-learning, it can be an effective tool in improving education under difficult circumstances. Online education can provide opportunities for students to access educational resources easily, and can contribute to enhancing communication between teachers and students. E-learning can also play a role in developing students’ technology skills, which is important in our modern era. In 2019, the Faculty of Science at the University of Gharyan partially implemented online learning as a response to COVID-19 pandemic, and this program continued for two academic terms. Therefore, the paper aims to highlights both the advantages and limitations of E-learning within the environment of university education in Libya. Methods. Student data from the science college was collected over six academic terms from 2019 to 2022 will be analyzed. Results. Overall, it is observed that in the academic year 2019-2020, which implemented distance learning, recorded the highest number of students, approximately 1800, while in the two subsequent years where traditional classroom seats were used. A decrease in the number of students was noted. Conclusion. E-learning can be effective and suitable for students in Gharyan University, particularly in subjects that do not require practical experiments or direct interaction, despite, its quality may be influenced by various factors.